A Case of Buspirone Demonstrating Immediate and Sustained Benefit in a Man With Lifelong Non–Rapid-Eye-Movement Parasomnias. Issue 2 (March 2019) - Mallapareddi, Arun; Varghese, Ranji
Abstract : Background: Non–rapid-eye-movement (NREM) parasomnias are disorders of sleep ranging from confusional arousals to sleepwalking and sleep-related eating disorders. Historically, antidepressants and benzodiazepines were recommended in treatment of NREM parasomnias. In this case report, we are reporting the use of buspirone in a patient with NREM parasomnias, which produced substantial resolution of symptoms. Case Presentation: A 38-year-old man presented with confusional arousals and somnambulism. In addition, the patient had significant anxiety with work-related stress. Given the patient's concerns of side effect profile of other medications indicated in NREM parasomnias and the patient's history of anxiety, we started the patient on buspirone. The patient had significant improvement in his symptoms immediately after starting the medication with sustained relief from symptoms. Conclusion: Buspirone can be considered an effective alternate treatment option for NREM parasomnias when other medications are not preferred or cannot be prescribed.